Should Individuals Choose their Own Incentives? Evidence from a Mindfulness Meditation Intervention - Andrej Woerner; Giorgia Romagnoli; Birgit M. Probst; Nina Bartmann; Jonathan N. Cloughesy; Jan Willem Lindemans (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Traditionally, incentives to promote behavioral change are assigned rather than chosen. In this paper, we theoretically and empirically investigate the alternative approach of letting people choose their own incentives from a menu of increasingly challenging and rewarding options. When individuals are heterogeneous and have private information about their costs and benefits, we theoretically show that leaving them the choice of incentives can improve both adherence and welfare. We test the theoretical predictions in a field experiment based on daily meditation sessions. We randomly assign some participants to one of two incentive schemes and allow others to choose between the two schemes. As predicted, participants sort into schemes in (partial) agreement with the objectives of the policy maker. However, in contrast to our prediction, participants who could choose complete significantly fewer sessions than participants that were randomly assigned. Since the results are not driven by poor selection, we infer that letting people choose between incentive schemes may bring in psychological effects that discourage adherence.
Keywords: C09; D03; D08; I01; 330; monetary incentives; dynamic incentives; field experiment; mental health